The Influence of the make a Match Learning Model on the German Writing Ability of Class XI Science Students at SMA YP HKBP PematangSiantar - Firginia Magdalena Simangunsong; Tarida Alvina Simanjuntak; Lydia Purba (International Journal of Educational and Psychological Sciences, 2023)
Objective study This For see p the influence of the learning model Make A Match against Skills write Language German Student Class XI Science SMA YP HKBP PematangSiantar. Study This use method quantitative with type study approach experiment And design One Group Pretest-Posttestresearch. Population in study This is student Class XI has 34 people. Sample used _ _ as many as 19 people, namely student class XI Science SMA YP HKBP PematangSiantar . Conclusion study This is a learning model Make A Match is influential to ability write Language German student class XI Science SMA YP HKBP PematangSiantar . That thing proven with enhancement average student score on during the pretest it was 52.63 under KKM and on at posttest it was 85.00 above the KKM. As for results test normality of value data The pretest significance is 0.053 and _ mark posttest significance of 0.067 , so concluded mark significance (Sig.) > 0.05 then the research data the normally distributed . Based on results data analysis and hypothesis that in test , known that learning model Make A Match influential to Skills write students . That thing proven with results analysis test hypothesis statistics with paired samples test generated mark significance equal to 0.001< 0.05 in meaning Sig value . (2-sided p) < 0.05, concluded that Ho was rejected and H 1 accepted . With that is the learning model Make A Match There is influence to Skills write student class XI Science SMA YP HKBP PematangSiantar